2018
DOI: 10.1155/2018/2031805
|View full text |Cite
|
Sign up to set email alerts
|

A First-Principles Study on Hydrogen Sensing Properties of Pristine and Mo-Doped Graphene

Abstract: The adsorption of H2 on the pristine and Mo-doped graphene was investigated by density functional theory (DFT) calculations. The structural and electronic properties of H2-graphene systems were studied to understand the interaction between H2 molecule and graphene-based material. Our calculation results showed the pristine graphene was not an ideal sensing material to detect H2 molecule as it ran far away from the pristine graphene surface. Different with pristine graphene, the Mo-doped graphene presented much… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…44 Similar results were also found in the Mo-doped or Pd-doped graphene sheets. 24,45 In the following research, the hydrogen molecules with different orientations were placed on the built nanoakes to investigate the interactions between the hydrogen gas and the PGNF (or CrGNF). Two typical adsorption modes were constructed for one hydrogen molecule adsorbed on PGNF (or CrGNF): (i) the hydrogen molecule was parallel to the nanoake with H atom above the active site (C atom for PGNF or Cr atom for CrGNF); (ii) the hydrogen molecule was perpendicular to the nanoake with the H atom above the active site.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…44 Similar results were also found in the Mo-doped or Pd-doped graphene sheets. 24,45 In the following research, the hydrogen molecules with different orientations were placed on the built nanoakes to investigate the interactions between the hydrogen gas and the PGNF (or CrGNF). Two typical adsorption modes were constructed for one hydrogen molecule adsorbed on PGNF (or CrGNF): (i) the hydrogen molecule was parallel to the nanoake with H atom above the active site (C atom for PGNF or Cr atom for CrGNF); (ii) the hydrogen molecule was perpendicular to the nanoake with the H atom above the active site.…”
Section: Resultsmentioning
confidence: 99%
“…9,22,23 The theoretical and experimental studies of Yang et al showed that the hydrogen storage capacity of the microporous carbon-based material could be signicantly enhanced by modied with Ru due to the spillover effect. 24 Fan and his workmates have also done a rst-principles study on the hydrogen storage properties of the Sc-decorated graphene. They found that there were six H 2 molecules in maximum adsorbed on the modied Sc atom.…”
Section: Introductionmentioning
confidence: 99%
“…In accordance with previous studies, pristine graphene has an inactive π-conjugation, which is not sensitive in the adsorption of molecules. [71][72][73] In fact, the pristine graphene is not capable to chemically bind molecular formic acid on its surface. Another possible way to adsorb FA is through a dissociative adsorption (DA),…”
Section: Fa Adsorptionmentioning
confidence: 99%
“…In line with previous studies, the graphitic areas possess an inactive p-conjugation, not sensitive to adsorption of molecules. 64,[90][91][92] Only single vacancies showed a favourable (exothermic) interaction with ammonia, indicating that a r( r BCP ) smaller than 0.6 e À A À3 defines the active sites on carbon surfaces. Combining the Laplacian of charge density analysis and the performed tests with NH 3 , we were able to identify C 3 , C 3 0 and C 7 in the single vacancy system as possible active sites (Fig.…”
Section: Hydrazine Adsorptionmentioning
confidence: 99%